Genomic Analysis of Mesorhizobium loti Strain TONO Reveals Dehalogenases for Bioremediation - Sefatullah Zakary; Habeebat Adekilekun Oyewusi; Fahrul Huyop (Journal of Tropical Life Science, 2021)
Halogenated compounds are extensively utilized in different industrial applications such as pesticides and herbicides and cause severe environmental problems because of their toxicity and persistence. Degradation of these compounds by the biological method is a significant method to reduce these recalcitrant. Mesorhizobium loti is important for nitrogen fixation in legume roots. Up to now, there is no report to indicate M. loti can produce dehalogenase enzymes. Thus, a total of twenty-five genomes of M. loti strains from the National Center for Biotechnology Information (NCBI) were analyzed. These strains notably carry dehalogenase genes and were further investigated. The relative ratio of haloalkane and haloacid dehalogenase type II or L-type from all twenty-five genomes was 26% and 74%, respectively, suggesting type II dehalogenase is common. Surprisingly, only M. loti strain TONO carries four dehalogenases and therefore it was further characterized. The chromosome of M. loti strain TONO contains four haloacid dehalogenase type II genes namely, dehLt1 (MLTONO_2099), dehLt2 (MLTONO_3660), dehLt3 (MLTONO_4143), and dehLt4 (MLTONO_6945), and their corresponding enzymes were designated as DehLt1, DehLt2, DehLt3, and DehLt4, respectively. The only haloalkane dehalogenase gene (MLTONO_4828) was located upstream of the dehLt3 gene and its amino acid share 88% identity with DmlA of Mesorhizobium japonicum MAFF 303099. The putative haloacid permease gene designated as dehrPt (MLTONO_0284) was located downstream of the dehLt1 and its amino acids show 69% identity with haloacid permease of Rhizobium sp. RC1. The gene encoding helix-turn-helix (HTH) motif family DNA-binding protein regulator and LysR family transcriptional regulator genes were also identified, possibly for regulatory functions. The genomic studies as such, have good potential to be screened for ne